Muscle-specific kinase levels in blood are an early diagnostic biomarker for SOD1-93A mouse model of ALS - Shuuichi Mori; Heying Zhou; Takuya Omura; Hiroki Tsumoto; Yuri Miura; Kazuhiro Shigemoto (Frontiers in Neurology)
Neuromuscular junction (NMJ) denervation is an early event preceding motor neuron loss in amyotrophic lateral sclerosis (ALS). Progressive loss of the NMJ leads to irreversible muscle weakness and atrophy. Muscle-specific kinase (MuSK), locally expressed at the postsynaptic membrane of the NMJ, is activated by agrin released from motor nerve terminals and is essential for NMJ maintenance and regeneration. Here, we found that the progression of NMJ denervation prior to the onset of muscle weakness in SOD1-93A mouse model of ALS correlated with increased serum MuSK immunoreactivity and elevated MuSK expression throughout the skeletal muscle. Our results suggest that neuromuscular failure associated with the onset of muscle weakness increases MuSK expression throughout the muscle, which is subsequently cleaved by proteolytic enzymes to increase MuSK immunoreactivity in the blood. These results demonstrate that the level of serum MuSK immunoreactivity may indicate the early phase of NMJ denervation and serve as a biomarker for assessing the progression of other types of ALS and therapeutic benefits in preclinical studies.